Osteoimmunomodulatory effects of biomaterial modification strategies on macrophage polarization and bone regeneration. Issue 3 (9th May 2020) - Xie, Yajuan; Hu, Cheng; Feng, Yi; Li, Danfeng; Ai, Tingting; Huang, Yulei; Chen, Xiaodan; Huang, Lijia; Tan, Jiali
Abstract: Biomaterials as bone substitutes are always considered as foreign bodies that can trigger host immune responses. Traditional designing principles have been always aimed at minimizing the immune reactions by fabricating inert biomaterials. However, clinical evidence revealed that those methods still have limitations and many of which were only feasible in the laboratory. Currently, osteoimmunology, the very pioneering concept is drawing more and more attention—it does not simply regard the immune response as an obstacle during bone healing but emphasizes the intimate relationship of the immune and skeletal system, which includes diverse cells, cytokines, and signaling pathways. Properties of biomaterials like topography, wettability, surface charge, the release of cytokines, mediators, ions and other bioactive molecules can impose effects on immune responses to interfere with the skeletal system. Based on the bone formation mechanisms, the designing methods of the biomaterials change from immune evasive to immune reprogramming. Here, we discuss the osteoimmunomodulatory effects of the new modification strategies—adjusting properties of bone biomaterials to induce a favorable osteoimmune environment. Such strategies showed potential to benefit the development of bone materials and lay a solid foundation for the future clinical application.